2013
DOI: 10.1111/nph.12251
|View full text |Cite
|
Sign up to set email alerts
|

ABSCISIC ACID INSENSITIVE3 regulates abscisic acid‐responsive gene expression with the nuclear factor Y complex through the ACTT‐core element in Physcomitrella patens

Abstract: Summary The phytohormone ABA and the transcription factor ABSCISIC ACID INSENSITIVE 3 (ABI3)/VIVIPAROUS 1 (VP1) function in protecting embryos during the desiccation stage of seed development. In a similar signaling pathway, vegetative tissue of the moss Physcomitrella patens survives desiccation by activating downstream genes (e.g. LEA1) in response to ABA and ABI3. We show that the PpLEA1 promoter responds to PpABI3 primarily through the ACTT‐core element (5′‐TCCACTTGTC‐3′), while the ACGT‐core ABA‐respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 67 publications
(98 reference statements)
3
36
0
Order By: Relevance
“…AtABI5 and AtRAV transgenic cotton exhibited higher or on par yields under WW greenhouse conditions and under drought stress in the field (Figure ), reduced the inhibition of photosynthesis and improved WUE in response to imposed drought (Figure ; Data S1), and enhanced carbon partitioned into leaves (Table ), roots (Table ) and stem (Tables S2, S3). Similar results have been reported recently for bZIPs, ABI3, NF‐Ys, MYBs, AP2, WRKY and Enhanced Drought Tolerance/HOMEODOMAIN GLABROUS11 (EDT1/HDG11) classes of TFs (Abdeen et al ., ; Kumimoto et al ., ; Li et al ., ; Liu and Howell, ; Ni et al ., ; Seo et al ., ; Yotsui et al ., ; Yu et al ., , ; Zhang et al ., ), underscoring that there are many possible modes of TF engineering for vegetative drought stress tolerance. Remarkably, the stacked lines of RAVxABI5 exhibited synergistic effects on maintaining A in response to imposed drought (Figure a) and concomitant adaptation to higher WUE by decreases in stomatal conductance G s , which translated into the generation of greater root mass (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…AtABI5 and AtRAV transgenic cotton exhibited higher or on par yields under WW greenhouse conditions and under drought stress in the field (Figure ), reduced the inhibition of photosynthesis and improved WUE in response to imposed drought (Figure ; Data S1), and enhanced carbon partitioned into leaves (Table ), roots (Table ) and stem (Tables S2, S3). Similar results have been reported recently for bZIPs, ABI3, NF‐Ys, MYBs, AP2, WRKY and Enhanced Drought Tolerance/HOMEODOMAIN GLABROUS11 (EDT1/HDG11) classes of TFs (Abdeen et al ., ; Kumimoto et al ., ; Li et al ., ; Liu and Howell, ; Ni et al ., ; Seo et al ., ; Yotsui et al ., ; Yu et al ., , ; Zhang et al ., ), underscoring that there are many possible modes of TF engineering for vegetative drought stress tolerance. Remarkably, the stacked lines of RAVxABI5 exhibited synergistic effects on maintaining A in response to imposed drought (Figure a) and concomitant adaptation to higher WUE by decreases in stomatal conductance G s , which translated into the generation of greater root mass (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The reporter construct proEm-GUS and its mutation constructs, proEm(mABRE)-GUS, proEm(mRY)-GUS, and proEm(mABRE/mRY)-GUS, were described in detail previously (Sakata et al, 2010). The 4xABRE-GUS construct has four ACGT-core repeats, AGCTCCACGTGTCGGCA, upstream of the minimal promoter of PpLEA1 (Yotsui et al, 2013). The cells were bombarded with DNAs of the effector and reporter constructs and the Ubi-LUC reference constructs coated on 1-mM gold particles using the PDS-1000He particle delivery system (Bio-Rad, Hercules, CA).…”
Section: Chemicals and Plant Materialsmentioning
confidence: 99%
“…We also note that significantly higher amounts of ABA were measured in desiccation tolerant protonemata compared to desiccation tolerant gametophores, suggesting that the two tissues might have different thresholds for response to the same stress. This idea is supported by Zhang et al (2015) who showed that expression levels of nuclear factor YC5 (PpNF-YC5), which acts synergistically with ABI3 in regulation of ABA responses (Yotsui et al 2013), differed widely among P. patens developmental stages, with unstressed gametophores having from 6-to 120-fold the amounts detected in protonemata. Perhaps this suggests that gametophores are already primed to respond to dehydration, while protonemata require additional ABA or time to respond, or perhaps it reflects developmental differences in the sensitivity to the hormone.…”
Section: Discussionmentioning
confidence: 92%